Analysis of the Role of Coorporate Image in Mediated Marketing Communications of Public Sector Services towards Public Trust (Study of the PMPTSP Service of Buton Selatan District) - Wa Ode Asrina Azizah Tasrif; Fauziah Umar; Syamsuddin Syamsuddin (Budapest International Research and Critics University, 2023)
The type of research used in this study is a type of correlational research. The research was conducted at the offices of the Investment and PTSP Office of South Buton Regency. According to Sugiyono (2019) population is a generalization area which consists of: objects/subjects that have certain quantities and characteristics set by researchers to study and then draw conclusions. The number of samples for this study was 90. In this study using accidental sampling techniques or other terms Random sampling. Data collection was carried out through questionnaires, observations, and interviews. This study was tested using Lenear Regression Analysis and Moderated Regression Analysis with the SPSS application; the results of this study indicate that communication has a positive and significant influence on government public trust. More interestingly, corporate image is proven to play an important role as a moderator in this relationship. These findings underscore the importance of transparent and open communication, as well as a positive corporate image in building and strengthening positive relations between government and society. The implication of this research is the need for the government to develop an effective communication strategy and maintain a positive image in order to strengthen the level of public trust in the government.